Fundamentals of Entrepreneurship (ENT300) : Printing Service Business / Afifah Athirah Saini ... [et al.] - Saini, Afifah Athirah; Clifton, Clarissa Eleanor; Batnon, Nadine Drew-Ann; Salam, Nur Atikah; Basuini, Muhammad Azizi (2019)
We are deciding to open printing services business as our business opportunity. The reason for choosing this printing business because printing is on huge demand across the globe. Thus, it can be ultimate source of income for us to start a printing business. Those various needs and wants of the costumers give use the opportunity to start a new business. We found that the strategic location with a huge business opportunity is Samarahan. Our business will be the most customer friendly start-up company in Samarahan where we provide printing services such as paper photocopy, t-shirt and banner.